Optimized GNSS RTK measurement planning for effective point occupation via heuristic analysis. Issue 1 (6th March 2017) - Bartonek, Dalibor; Bures, Jiri; Svabensky, Otakar
Abstract : Purpose: This paper aims to deal with the formulation of the technological principle for precise positioning using global navigation satellite systems (GNSS) in railway engineering during construction and maintenance of a railway line and its spatial position. Solution of optimal route is based on finding the shortest Hamiltonian path in the graph method with additional conditions in nodes. Design/methodology/approach: The core of the algorithm is a dynamic data structure which is based on events list. The optimization of field measurement solves the time demands and brings economic effectiveness. Findings: The technology enables to determine the precise position with absolute difference limit from 10 to 15 mm within GNSS CZEPOS permanent network in the territory of Czech Republic. Research limitations/implications: Technology is the result of applied research. Practical implications: This technology innovates the current procedure of geodetic control network determination used by Railway Infrastructure Administration (state organization) in Czech Republic. Originality/value: The event means measurement at a given track point and time for a specified duration of observation. The algorithm was realized in Borland Delphi. The optimization of field measurement solves its time demands and increases economic effectiveness. The technology enables precise position determination with absolute difference limit from 10 to 15 mm within GNSS CZEPOS permanent network in the territory of Czech Republic. It has been verified in field selected electrified and non-electrified railway lines.